CASH CONVERSION CYCLE EFFECTS ON PROFITABILITY OF MALAYSIAN PLANTATION SECTOR - Nazaria, Md. Aris; Brenda Nu, Minggu; Tan, Yuin Weng; Lim, Pei Jia; Ahmad Syubaili, Mohamed (UNIMAS Publisher, 2023)
The cash conversion cycle (CCC) is a crucial indicator in determining how efficiently a firm can turn its inventory into sales and subsequently into cash. Data from 43 firms listed in Bursa Malaysia from 2016 to 2019 were used to study the relationship between the CCC and profitability. The determinants for CCC are the days sales outstanding (DSO), days payables outstanding (DPO), and days inventory outstanding (DIO) while profitability is represented by the return on assets (ROA) of the firms. The data were collected from the published annual reports and audited financial statements of the local plantation firms and analyzed using EViews version 10. The result reported that DSO positively influences profitability significantly. DIO also reported a positive influence on profitability but the relationship is insignificant. On the other hand, DPO has an adverse effect on profitability and the relationship is insignificant. The findings provide useful information for the Malaysian government, investors, and policymakers in developing effective policies, rules, or regulations to promote economic productivity, growth, and the best plantation financing decision.